Factors affecting awareness of emergency contraception among college students in Kathmandu, Nepal - Adhikari, Ramesh (BioMed Central, 2009)
BACKGROUND: In Nepal, Emergency Contraception (EC) could play a critical role in reducing unintended pregnancies, but very few people aware about it. This paper aims to investigate the level of awareness and factors influencing awareness of EC among college students. METHODS: A cross-sectional study was carried out in April-May 2006. Structured self-administered questionnaires were administered to 1,137 college students (573 males and 564 females) in Kathmandu valley. The association between awareness of EC and the explanatory variables were first assessed in bivariate analysis using the Chi-square test. The associations were further explored using a multivariate logistic analysis. RESULTS: Only about two-thirds of college students (68%) had ever heard about EC. Bivariate analysis shows that males were more aware (72%) of EC than were females (64%). Similarly, the awareness level was significantly higher among younger, unmarried youth who were from outside Kathmandu Valley, who lived with friends, and who had received reproductive health (RH) education in school/college. The study also found that students' sex, permanent place of residence (district), and RH education are significant predictors of awareness of EC. Males are 1.5 times more likely to be aware of EC compared to females. Furthermore, students who lived in Kathmandu Valley were 41% less likely to be aware of EC than were students from outside Kathmandu Valley. On the other hand, those students who received RH education in school/college were almost nine times more likely to be aware of EC compared to those who did not receive such education. CONCLUSION: Awareness of the EC is low among college students in Nepal. Health education initiatives should target students as they are more likely to be sexually active. There is a need to further educate students about EC which can help to reduce unintended pregnancies, many of which result in unsafe abortion and take a large toll on women's health.